Cultivation has selected for a wider niche and large range shifts in maize - Rujing Yang; Runyao Cao; Xiang Gong; Jianmeng Feng (PeerJ, 2022)
Background Maize (Zea mays L.) is a staple crop cultivated on a global scale. However, its ability to feed the rapidly growing human population may be impaired by climate change, especially if it has low climatic niche and range lability. One important question requiring clarification is therefore whether maize shows high niche and range lability. Methods We used the COUE scheme (a unified terminology representing niche centroid shift, overlap, unfilling and expansion) and species distribution models to study the niche and range changes between maize and its wild progenitors using occurrence records of maize, lowland teosinte (Zea mays ssp. parviglumis) and highland teosinte (Zea mays ssp. mexicana), respectively, as well as explore the mechanisms underlying the niche and range changes. Results In contrast to maize in Mexico, maize did not conserve its niche inherited from lowland and highland teosinte at the global scale. The niche breadth of maize at the global scale was wider than that of its wild progenitors (ca. 5.21 and 3.53 times wider compared with lowland and highland teosinte, respectively). Compared with its wild progenitors, maize at global scale can survive in regions with colder, wetter climatic conditions, as well as with wider ranges of climatic variables (ca. 4.51 and 2.40 times wider compared with lowland and highland teosinte, respectively). The niche changes of maize were largely driven by human introduction and cultivation, which have exposed maize to climatic conditions different from those experienced by its wild progenitors. Small changes in niche breadth had large effects on the magnitude of range shifts; changes in niche breadth thus merit increased attention. Discussion Our results demonstrate that maize shows wide climatic niche and range lability, and this substantially expanded its realized niche and potential range. Our findings also suggest that niche and range shifts probably triggered by natural and artificial selection in cultivation may enable maize to become a global staple crop to feed the growing population and adapting to changing climatic conditions. Future analyses are needed to determine the limits of the novel conditions that maize can tolerate, especially relative to projected climate change.